Formulation Stategies for Vocational High School in Surabaya ( Case Study: SMKS â€œXâ€) - Limbong, Sucipto; Artama Wiguna, I Putu (Institut Teknologi Sepuluh Nopember, 2020)
This research focuses on strategic planning conducted at one of the private vocational high schools in Surabaya. Vocational school is one of the services in the education sector that aims to prepare students to work in specific fields. At this time, the number of students enrolling has decreased, so the need for proper strategic planning for schools in increasing the number of students. The method used in this study is the formulation of internal and external factors using the IFE and EFE matrices as the input stage and followed by determining the weights for each factor using pair comparison. In the next stage, this study uses the SWOT matrix as a strategy matching stage. The results showed the value of the IFE matrix. Schools had a total rating of 2.5, while the scores on the EFE matrix, schools had a total rating of 2.878. Based on an analysis of internal and external factors using the SWOT matrix, several alternative strategies can be obtained including Development of New Departments; Establish relationships with junior high schools in the same institution; Development of Learning Processes; Increased School Promotion; Maximizing BOS Funds; Collaboration with DU / DI; School Resource Development; School Culture Development and School Program Improvement; Improved School Performance and Quality. For the design of the strategy map obtained from four perspectives, including: (a) Financial Perspectives: Regular Provision of Budgets, Income Levels, Utilization of BOS Funds and School Imagery; (b) Customer Perspective: Number of Students, Customer Satisfaction, and School Quality; (c) Internal Business Perspectives: Marketing Development, Innovation, Process, After Sales Service, and Relationship Enhancement with DU / DI; (d) Learning and Growth Perspectives: Teacher / Staff Satisfaction, School Financial Management Development, Information System Capability, Teacher / Staff Development, and School Culture Development.